2019
DOI: 10.3390/electronics8111269
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of Scratch and App Inventor with Regard to Learning Computational Thinking Concepts

Abstract: Scratch and App Inventor are two of the most widely used block-based programming languages for young students. These are educational languages which allow students to program easily by dragging and dropping their code blocks. One question that arises in relation to these educational languages is which of them would be more helpful in fostering computational thinking. It is difficult to answer this question because each language has its own advantages. In this paper, we propose a novel rubric based on Dr. Scrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…The increase in the number of participants over the years from 105 in 2016 to 124 in 2017 and 135 in 2018 confirmed that the contest is gaining in popularity in the education sector. Our findings were congruent with the study of Nouri et al, [40] which highlighted that teaching programming to k-9 students not only develops CT skills but alsopromotes skills and attitudes of a more general character that are strongly associated with 21 st -century skills and digital competence/literacy. Moreover, Turchi et al, [5] argued that embracing a playful experience in programming could support pupils' progress in STEM subjects by learning CT skills while enjoying the experience.…”
Section: Comments From Studentssupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in the number of participants over the years from 105 in 2016 to 124 in 2017 and 135 in 2018 confirmed that the contest is gaining in popularity in the education sector. Our findings were congruent with the study of Nouri et al, [40] which highlighted that teaching programming to k-9 students not only develops CT skills but alsopromotes skills and attitudes of a more general character that are strongly associated with 21 st -century skills and digital competence/literacy. Moreover, Turchi et al, [5] argued that embracing a playful experience in programming could support pupils' progress in STEM subjects by learning CT skills while enjoying the experience.…”
Section: Comments From Studentssupporting
confidence: 92%
“…It also improves the level of concentration and encourages collaborative learning. Furthermore, Nouri et al, [40] stated that computational thinking, digital competence, and 21 st -century skills of students were enhanced when they learnt programming.…”
Section: Results Of Semi-structured İnterviewsmentioning
confidence: 99%
“…The recognition of sadness and fear is more dependent on the information provided by the eyes, the recognition of surprise and calm emotions is more dependent on the information provided by the mouth, and the recognition of happiness, anger, and disgust is more dependent on the eyes and mouth [ 39 41 ]. The degree of dependence on the provided information is indistinguishable, among which the recognition of happy and angry emotions relies more on eye information, and the recognition of disgust emotions relies more on mouth information [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to investigate the factors that lead to students learning difficulty in programming. Several studies already examine the learning of specific concepts when developing apps with App Inventor, including procedural abstraction concepts [31], events [9], programmatic sophistication [32], effectiveness [33], or appropriateness [10] of App Inventor as an educational environment. Others study the learning progression of students in computing courses in K-12, e.g., Xie and Abelson [34], who analyze the relationship between the progression of skill in using App Inventor functionality and in using computational thinking concepts as learners create more apps.…”
Section: Introductionmentioning
confidence: 99%